Social management problems and economic performance in peruvian smes belonging to gamarra‐type trading centers (2006‐2015) - Esquives Chunga, Nancy Margot (2017)
In the present context, all business activities need to reach, in addition to economic and environmental viability, social legitimacy. The numerous conflicts sparked by economic activities in different areas of the country clearly demonstrate the critical importance of getting the acceptance of the populations and the local authorities of the area in which the activity is performed. The SMEs of the Gamarra trading center are not oblivious to this reality, and realize that they need to obtain and maintain their social viability in the environment where they operate. While acceptance is not a guarantee of business success, it contributes to create the conditions for the good neighborly relations that facilitate social and environmental management. Given the socioeconomic conditions that characterize this sector, in order to achieve this social viability, SME leaders must keep in mind from the start that social viability requires a sustained commitment over time. This must be reflected in shared efforts during the planning of the relationship and the support activities with the local populations and their authorities. Support by the local population for SME activities in the Gamarra trading center is not a natural process. To achieve it, it is necessary to develop specific, well planned activities and to count with sufficient financial, technical and human resources. Hopefully, these efforts should allow the building of strategic partnerships between the community, the local authorities and the businesses, which would bring forward the identification, definition and implementation of local sustainable development projects. The present article, called "Social management problems and economic performance in Peruvian SMEs belonging to Gamarra‐ type trading centers (2006‐2015)", is an important tool containing basic concepts about what are social management, conflict management, social responsibility, sustainable development and communication, among others. Its goal is to establish a standardized level of knowledge to contribute to the development of social management strategies, in order to reconcile local development, the population welfare and business success, within the area of influence of the SMEs of the Gamarra trading center.